Effect of Benzylaminopurine (BAP) pulsing on in vitro shoot multiplication of musa acuminata (banana) cv. berangan - Jafari, N.; Othman, R.Y.; Khalid, Norzulaani (Academic Journals, 2011)
MS (Murashige and Skoog) media supplemented with benzylaminopurine (BAP) showed that the number of bud formation in shoot cultures of Musa acuminata cv.Berangan during the initiation stage increased proportionately with the concentrations used (11, 22 and 33 Î¼M). However, the highest concentration of BAP (33 Î¼M) simultaneously increased the formation of abnormal shoots. After the first apical bud appeared, explants were transferred to MS medium with lower concentrations of BAP either with or without indole acetic acid (IAA). Proliferation media supplemented with IAA showed enhanced shoot multiplication and elongation but did not help to reduce the abnormality index that occurred